Local vaccination reaction misdiagnosed as physical abuse. - Williams, R.E.A.; MacKie, R.M. (European Journal of Pediatric Dermatology, 2018)
The misdiagnosis of physical abuse in a child suffering from a local vaccination reaction due to aluminium hypersensitivity caused psychological and social trauma in his family for over a year before a dermatological opinion was sought and the correct diagnosis rapidly made.